Acute effect of empagliflozin on serum uric acid – a subanalysis of the EMPAG-HF trial (effects of empagliflozin on diuresis and renal function in patients with acute decompensated heart failure). (3rd October 2022) - Bogoviku, J; Nguyen, T D; Westphal, J G; Haertel, F; Grund, S; Aftanski, P; Moebius-Winkler, S; Busch, M; Schulze, P C
Abstract: Background: Elevated levels of uric acid (UA) have been associated with worsening of outcomes in cardiovascular and renal disease and may lead to gout. Patients with acute decompensated heart failure (ADHF) may develop hyperuricemia under intensified diuretic treatment. In this setting, the effect of empagliflozin on serum uric acid remains unknown. Aim/Purpose: The aim of this subanalysis in patients with ADHF was to assess how additive treatment with empagliflozin influences the concentration of serum uric acid and potential related outcomes. Methods: In the single-center, prospective, double-blind, placebo-controlled EMPAG-HF trial, patients with ADHF were screened and randomized within 12 hours following hospital admission to receive either empagliflozin 25 mg or placebo in addition to standard medical treatment over five days. Sixtypatients (mean age 74, 7±9, 9, 39% female) were enrolled and randomized 1:1 irrespective of left ventricular ejection fraction or the presence of diabetes. UA in serum was determined daily and renal handling of UA was evaluated by fractional excretion of UA (FEUA). Two-way mixed ANOVA and Wilcoxon rank-sum test were used for statistical analyses. Results: The empagliflozin group comprised 30 patients and the placebo group comprised 29 patients. There were no differences in baseline patient characteristics including LVEF, NT-proBNP, eGFR, HbA1c. In the placebo group, UA increased from baseline 487.86±32.21 μmol/l to 500.38±28.37 μmol/l at day (d) 2 (p=0.045), 512.36±29.43 μmol/l at d3 (p=0.018), and 518.46±31.14 μmol/l at d4 (p=0.021). By contrast, in the empagliflozin group, UA tended to decrease compared to baseline and was significantly lower compared to placebo at d3 (436.08±23.94 vs. 512.36±29.43 μmol/l, p=0.049), d4 (423.20±24.12 vs. 518.46±31.14 μmol/l, p=0.018), and d5 (423.17±24.75 vs. 508.62±31.08 μmol/l, p=0.037). Serum UA returned to baseline levels in both groups 30 days after cessation of empagliflozin. The reduction of UA in the empagliflozin group was associated with a significant enhancement in FEUA (5.49±0.81% vs. 9.38±1.07%, p=0.004). Conclusion: Our data suggest that the additive treatment with empagliflozin in patients with acute decompensated heart failure lowers the levels of serum uric acid compared to loop diuretics alone. This effect may be attributed to an improved renal elimination of UA and a better preservation of kidney function. It remains to be clarified whether this uricosuric effect of empagliflozin also contributes to its prognostic benefits in heart failure. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Department of Internal Medicine I, Division of Cardiology, Angiology and Intensive Medical Care, University Hospital Jena, Friedrich-Schiller-University, Jena, Germany) Boehringer Ingelheim Inc.